A fluorescent Ce-EDTA probe for the sensing of ascorbic acid and lysine in real samples. Issue 21 (30th August 2022) - Rajpal,; Kumar, Ashish; Jana, Subhajit; Singh, Priya; Prakash, Rajiv
Abstract : In the present work, a fluorescent probe based on an aqueous dispersion of coordination complex Ce-EDTA is utilized for sensing carboxyl compounds. Abstract : In the present work, a fluorescent probe based on an aqueous dispersion of coordination complex Ce-EDTA is utilized for sensing carboxyl compounds. Ce-EDTA is synthesized herein by a hydrothermal method with the help of stoichiometric ratios of cerium (Ce) (+iii ) salts and green ligand ethylenediamine N, N, N, N tetra-acetic acid (EDTA). In Ce-EDTA, the Ce ion is surrounded by hexadentate EDTA and three labile aqua ligands, evidenced by FT-IR, XPS, and UV-visible spectroscopy. It exists in the form of polygonal microplates, as apparent by SEM. The sensing mechanism is proposed by choosing carboxyl groups as a part of the ring and open chain. Under the optimized situations, the fluorescence intensities of Ce-EDTA are monitored towards various concentrations of l -lysine (Lys) and ascorbic acid (AA) in these regards. They exhibit a linear response from 20.29 μM to 251.74 μM and 5.62 μM to 60.87 μM with a linear correlation coefficient ( R 2 ) of 0.98 and 0.99, respectively. The lower limit of detection is observed as 3.6 μM in the case of Lys and 2.04 μM in the case of AA. The as-prepared probe exhibits suitability for selectivity of AA and Lys in the presence of various interfering agents as well as in real samples for the detection of AA in orange and Lys in soybean seed.